THE INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE AND INTERNAL CONTROL ON INDICATIONS OF FRAUD IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Husaeni, Uus Ahmad Ahmad (IJIBE (International Journal of Islamic Business Ethics), 2021)
This article aims to analyze the implementation of ICG (Islamic Corporate Governance) and Internal Control on indications of fraud at Islamic Commercial Banks in Indonesia. The method used in this study is to use quantitative analysis with technical data analysis using multiple linear regression. The data used is secondary data obtained from Islamic banking financial reports, amounting to 60 data. The conclusion in this article is the influence of Islamic Corporate Governance which is proxied by the variables of the implementation of DPS duties and responsibilities, the performance of duties and responsibilities of the board of directors, and internal control, on the dependent variable, namely, the indication of fraud in Islamic Commercial Banks in Indonesia of 46.1 percent while the rest 53.9 percent is influenced by other factors which are not used in this study